Design and developement of semi automatic canting tool (body design and mechanism) - Mohammad Muaz, Nordin (2012)
This thesis deals with the design and developement of new tool for making batik.The process of making batik are of two method, batik canting (hand drawn batik) and batik “chop” (batik stamp). Conventionally, in batik canting process, the molten wax are drawn onto fabric using a wooden, copper sprout tool which known as the “canting” or “tjanting”. Since Malaysia government are serious in promoting the industry of batik internationally, and there is need to strengthen the Small and Medium Industry (SME) of Malaysia, this project then is carried on. The main purpose of the project are to design and develop a new semi automatic canting tool. The term semi automatic is subjected to the combination of several processes in batik making process into a single tool. The idea is to have tool that enable the electrical heating and the drawing process done simultaneously. This will eliminate the process of conventional heating process using stove and the process of transferring the molten wax into the canting tool before the drawing process started. This study started by collecting all the information related to batik making process such as the canting tool, the steps on producing batik, and also the raw material related to batik making process. The information are collected through visit and also interview session. After all informations are sufficient enough, then the initial idea and design are developed. Throughout the project, SolidWork 2012 are used to do design and also simulation analysis on the tool. Prototyping of the tool are for functionality testing which evaluate the ergonomic design and drawing ability of the tool. The results are then analyze to see if the tool are well function or not. The findings are then summarized with some recommendations suggested to improve the tool.